Brain Oscillations and Functional Connectivity during Overt Language Production - Ewald, Arne; Aristei, Sabrina; Nolte, Guido; Rahman, Rasha A. (Frontiers in Psychology, 2012)
In the present study we investigate the communication of different large scale brain sites during an overt language production task with state of the art methods for the estimation of EEG functional connectivity. Participants performed a semantic blocking task in which objects were named in semantically homogeneous blocks of trials consisting of members of a semantic category (e.g., all objects are tools) or in heterogeneous blocks, consisting of unrelated objects. The classic pattern of slower naming times in the homogeneous relative to heterogeneous blocks is assumed to reflect the duration of lexical selection. For the collected data in the homogeneous and heterogeneous conditions the imaginary part of coherency (ImC) was evaluated at different frequencies. The ImC is a measure for detecting the coupling of different brain sites acting on sensor level. Most importantly, a non-vanishing ImC cannot be explained by mixtures of independent sources and must therefore reflect true interactions. After performing a grand average over 24 subjects we analyzed the ImC at all pairs of 56 EEG channels across all frequencies. Contrasting the two experimental conditions we found differences in interaction between left temporal and frontal areas and frontal and occipital areas in the theta band at 7Hz, and also smaller differences in the delta and beta band. These areas are well-known to play a major role in lexical-semantic language processes. Our findings demonstrate the feasibility of investigating interactive brain activity during overt language production.